Financial implications of using extracorporeal membrane oxygenation following heart transplantation. (11th December 2020) - Krishnamoorthy, Bhuvaneswari; Mehta, Vipin; Critchley, William; Callan, Paul; Shaw, Steve; Venkateswaran, Rajamiyer
Abstract: OBJECTIVES: Primary graft dysfunction after heart transplant is associated with high morbidity and mortality. Extracorporeal membrane oxygenation (ECMO) can be used to wean patients from cardiopulmonary bypass. This study retrospectively reviews a single-centre experience of post-transplant ECMO in regard to outcomes and associated costs. METHODS: Between May 2006 and May 2019, a total of 267 adult heart transplants were performed. We compared donor and recipient variables, ECMO duration and the incidence of renal failure, bleeding, infection and cost analysis between ECMO and non-ECMO groups. RESULTS: ECMO support was required postoperatively to manage primary graft dysfunction in 72 (27%) patients. The mean duration of ECMO support was 6 ± 3.2 days. Mean ischaemic times were similar between the groups. There was a significantly higher proportion of ventricular assist device explant to transplant in the ECMO group versus non-ECMO (38.2% vs 14.1%; P < 0.0001). ECMO patients had a longer duration of stay in the intensive care unit ( P < 0.0001) and total hospital stay ( P < 0.0001). Greater mortality was observed in the ECMO group ( P < 0.0001). The median cost of providing ECMO was £18 000 [interquartile range (IQR): £12 750–£24 000] per patient with an additional median £35 225 (IQR: £21 487.25–£51 780.75) for ITU stay whilst on ECMO. The total median cost per patient inclusive of hospital stay, ECMO and dialysis costs was £65 737.50 (IQR: £52 566.50–£95 221.75) in the non-ECMO group compared to £145 415.71 (IQR: £102 523.21–£200 618.96) per patient in the ECMO group ( P < 0.0001). CONCLUSIONS: Patients with primary graft dysfunction following heart transplantation who require ECMO are frequently bridged to a recovery; however, the medium and longer-term survival for these patients is poorer than for patients who do not require ECMO.